Barriers to Retention in Care among Adults with HIV in Developed Countries: An Integrative Review. - Sanders, Tea Nynne; Roed, Anna Katrine Haslund; Missel, Malene; Berg, Selina Kikkenborg; Nielsen, Susanne Dam; Olesen, Mette Linnet; Kirk, Ole (AIDS & Behavior, 2025)
Focusing on factors hindering viral suppression is essential for improving the health outcomes of people with Human Immunodeficiency Virus (HIV) and working towards ending the HIV/AIDS epidemic. The aim of this integrative review is to create an overview of barriers to retention in care among adults with HIV living in developed countries. Based on a systematic literature search across EMBASE, PubMed, Scopus, CINAHL, and PsycInfo, 4,089 studies of various methodology were identified. A total of 52 studies met the inclusion criteria. Quality assessment was performed using the Mixed Method Appraisal Tool. Based on thematic analysis, the following five main themes were identified as most common barriers to retention in care: financial challenges, logistical challenges, stigma, mental health problems, and substance use. The integrative review highlights that various factors can hinder retention in care and underscores that strategies to promote retention in care should be person-centered and targeted the individual person's barriers to retention in care.